Complete structural characterization of ceramides as [M−H]− ions by multiple-stage linear ion trap mass spectrometry - Hsu, Fong-Fu (Biochimie, 2016)
Ceramide is a huge lipid family consisting of diversified structures including various modifications in the fatty acyl chain and the long chain base (LCB). In this contribution, negative-ion ESI linear ion-trap multiple-stage mass spectrometric method (LIT MSn) towards complete structural determination of ceramides in ten major families characterized as the [M−H]− ions is described. Multiple sets of fragment ions reflecting the fatty acyl chain and LCB were observed in the CID MS2 spectrum, while the sequential MS3 and MS4 spectra contain structural information for locating the double bond and the functional groups, permitting realization of the fragmentation processes. Thereby, differentiation of ceramide molecules varied by chain length, the LCB (sphingosine, phytosphigosine, 6-hydroxy-sphingosine), and by the modification (α-hydroxy-, β-hydroxy-, ω-hydroxy-FA) can be achieved; and many isomeric structures in the biological specimen can be revealed in detail. •Complete structural characterization of ceramides in 10 subfamilies is presented.•Mass spectra from Linear ion-trap MSn reveals structural details and the mechanisms underlying the fragmentation processes.•Multiple sets of fragment ions regarding to fatty acid and long chain base substituents lead to confident structure assignment and isomer differentiation.•Isomeric structures in a biological specimen are identified.